The Intersection of Big Data and Anthropology - Copple, Ethan (Kansas State University. Dept. of English, 2019)
The intersection of big data and anthropology is important for both academics and private sector leaders in both fields to understand due to the joint applications and capabilities created. Through the inter-disciplinary intersection, both big data and anthropology could be mutually and greatly impacted, but due to the widespread perception that the fields function aversely, seemingly few people are investigating. The intersection has already illuminated fascinating research and practical applications that could revolutionize how data is interpreted and is utilized both in academia and the private sector. The literature review will seek to showcase these applications through a number of both academic and nonacademic sources which relate anthropology and big data.
Kirmser Undergraduate Research Award - Individual Non-Freshman category, honorable mention
Keywords: Big Data; Anthropology; Data Interpretation; Data Applications